Whatever: Giorgio Agamben's gender trouble. Issue 5 (4th May 2021) - Thomson, Stephen
ABSTRACT: Feminist scholars interested in the political ideas of Giorgio Agamben have had to negotiate the 'gender-blindness' of his writing and the absence from his theory of women's bodies. They are nevertheless sometimes prepared to appropriate the concept of 'bare life' as if it were in itself relatively unaffected by its original frame, and easily extricated from it. On the contrary, I argue that gender difference poses fundamental problems for the schema of 'bare life'. Female bodies are not simply missing from Homo Sacer, but included as an absence in the universalising 'man' that is the protagonist of Agamben's discourse. As such they play an occluded role in founding Agamben's authority. I explore the implications of this further in more recent works where the female body does play an explicit role, in the form of the 'nymph'. Here I show that this insistently feminine figure, whose political implications have not often been considered, acts as a specular supplement to an ostensibly universal, but implicitly masculine, 'man'. I conclude by exploring the drama of castration in Agamben's work on art as a function of the mastery to which his writing aspires, and which sits uneasily with his critique of sovereignty.